HUBUNGAN ANTARA ETOS KERJA DENGAN OCB PADA KARYAWAN OUTSOURCING - Dina Chairina; Suci Rahma Nio (Jurnal Riset Psikologi, 2018)
Abstract: The relationship work ethic and OCB to employee outsourcing. This study aims to determine the relationship of work ethic with OCB on outsourcing employees at RSCM Medika Nusantara. The design used in this study is quantitative correlational. The population in this study were employees of outsourcing at RSCM Medika Nusantara with a total sample of 75 employees. The sampling technique used is saturated sampling. Data collection uses OCB scale with a reliability value of 0.893 and a work ethic scale with a reliability value of 0.895. Data were analyzed using simple linear regression techniques. From the results of the study showed a significant positive relationship between work ethic with OCB on outsourced employees at Cut Meutia Medika Nusantara Hospital with a value of F = 71,579 which had p <0.05 (p = 0.00) with a correlation coefficient (r) = 0.597 shows that the work ethic of outsourcing employees has a relationship to OCB.Keywords : Work ethic, organizational citizenship behavior (OCB), outsourcingAbstrak: Hubungan antara etos kerja dengan OCB pada karyawan outsourcing. Penelitian ini bertujuan untuk mengetahui hubungan etos kerja dengan OCB pada karyawan outsourcing di RSCM Medika Nusantara. Desain yang digunakan dalam penelitian ini adalah kuantitatif korelasional. Populasi dalam penelitian ini adalah karyawan outsourcing di RSCM Medika Nusantara dengan jumlah sampel sebanyak 75 karyawan. Teknik pengambilan sampel yang digunakan yaitu sampling jenuh. Pengumpulan data menggunakan skala OCB dengan nilai reliabilitas 0.893 dan skala etos kerja dengan nilai reliabilitas 0.895. Data dianalisis menggunakan teknik regresi linier sederhana. Dari hasil penelitian menunjukkan hubungan yang positif yang signifikan antara etos kerja dengan OCB pada karyawan outsourcing di RS Cut Meutia Medika Nusantara dengan nilai F = 71.579 yang memiliki p < 0,05 (p = 0,00) dengan nilai koefisien korelasi (r)=0.597 menunjukkan bahwa etos kerja pada karyawan outsourcing memiliki hubungan terhadap OCB.Kata kunci : Etos kerja, organizational citizenship behavior (OCB), outsourcing